2022
DOI: 10.1038/s41467-022-34088-w
|View full text |Cite
|
Sign up to set email alerts
|

Human mtRF1 terminates COX1 translation and its ablation induces mitochondrial ribosome-associated quality control

Abstract: Translation termination requires release factors that read a STOP codon in the decoding center and subsequently facilitate the hydrolysis of the nascent peptide chain from the peptidyl tRNA within the ribosome. In human mitochondria eleven open reading frames terminate in the standard UAA or UAG STOP codon, which can be recognized by mtRF1a, the proposed major mitochondrial release factor. However, two transcripts encoding for COX1 and ND6 terminate in the non-conventional AGA or AGG codon, respectively. How t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…These results show that mtRF1 is the release factor responsible for the recognition of noncanonical stop codons. This conclusion is supported by the work of two independent research groups who published their findings during the revision of this manuscript ( 25 , 29 ). However, these results also raise the question of how the unusual codon-recognition domain of mtRF1 accomplishes this task.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…These results show that mtRF1 is the release factor responsible for the recognition of noncanonical stop codons. This conclusion is supported by the work of two independent research groups who published their findings during the revision of this manuscript ( 25 , 29 ). However, these results also raise the question of how the unusual codon-recognition domain of mtRF1 accomplishes this task.…”
Section: Resultssupporting
confidence: 71%
“…The observed residual production of COX1 in the absence of mtRF1 (Fig. 1C) is likely because of the activity of rescue factor mtRF-R ( 20 , 25 ). Deletion of mtRF-R or ICT1 resulted in marked and general reduction of mitochondrial protein synthesis (fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies reported that mtRF1 is specifically responsible for translation termination of COX1, and thus for the biogenesis of complex IV (Fig. 1, left side) [8][9][10]. Loss of mtRF1 leads to a selective reduction in newly synthesized COX1 and to isolated complex IV deficiency.…”
Section: Termination Of Cox1 Translationmentioning
confidence: 99%
“…However, as these patients with usually undetectable levels of C12ORF65 display a general translation defect, mtRQC mediated by C12ORF65 seems to be generally involved in ribosome rescue and not selectively responsible for the release of stalled COX1‐translating ribosomes. Interestingly, the reduction in COX1 translation termination due to mtRF1 ablation specifically reduces the level of COX1 mRNA while all other mitochondrial transcripts remained unaffected [9,10]. The specific reduction in COX1 mRNA might reflect a feedback mechanism that prevents an overload of the mtRQC if mtRF1 is missing.…”
Section: Termination Of Cox1 Translationmentioning
confidence: 99%